Factors affecting strategic instructional leadership practices of school principals: Teachers’ perception - Ghavifekr, S.; Chellapan, K.; Sukumaran, K.; Subramaniam, A. (2014)
Instructional leadership is an important aspect of school principals. The roles of instructional leader in an educational organization are setting clear goals, managing curriculum, monitoring lesson plans, allocating resources and evaluating teachers regularly to promote student learning and growth. To improve the quality of an educational organization, an instructional leader should play his /her role and responsibility efficiently and effectively. The main purpose of this study was to identify the factors affecting instructional leadership practices of school principals. A quantitative method was used to collect the data. Accordingly, survey questionnaire was used as the main instrument to collect the data from the Youth Skills Training Institution randomly. The sample consisted of 100 teachers who are currently teaching technical and non-technical subjects in the training institution. Four domains were used as factors affecting the instructional practices, which are professional leadership, shared mission and clear goals, continued monitor of teacher progress and professional growth of the teachers. Findings shows that the four domain factors were really affect the instructional leadership practices. The findings of this study can be beneficial for policy and decision makers in the Ministry of Education, school management and administration as well as teachers.